A scoping review investigating the use of exposure for the treatment and targeted prevention of anxiety and related disorders in young people. Issue 2 (20th May 2022) - Teunisse, Alessandra K.; Pembroke, Lorna; O'Gradey‐Lee, Maddison; Sy, Megan; Rapee, Ronald M.; Wuthrich, Viviana M.; Creswell, Cathy; Hudson, Jennifer L.
Abstract: Background: Cognitive Behavioural Therapy (CBT) is the gold standard intervention for anxiety and related mental health disorders among young people; however, the efficacy of individual elements of CBT (e.g., exposure to feared stimuli) have received little scrutiny. Aims: This scoping review, informed by three stakeholder groups and a scientific advisory group, aimed to identify the nature and extent of the available research literature on the efficacy of exposure to feared stimuli, moderators of effectiveness in young people aged 14–24 years. Method: Three international stakeholder groups composed of clinicians ( N  = 8), parents/carers ( N  = 5) and youth with lived experience of anxiety ( N  = 7) provided input into study design and results. Using the PRISMA extension for scoping reviews, a search of MEDLINE/Ovid, PsycINFO, PubMed, CINAHL, SCOPUS, EMBASE, ERIC, and Health Collection (informit) was conducted using terms related to anxiety, ages 14–24, and exposure. Results: From 3508 unique abstracts, 64 papers were included for the review. While there was evidence for the efficacy of exposure as a treatment for youth anxiety disorders, fundamental gaps in knowledge of exposure in this age group were identified. Most studies examined post‐traumatic stress disorder, obsessive–compulsive disorder, and specific phobias with no randomised clinical trials uniquely evaluating exposure for the treatment of DSM‐5 anxiety disorders. Exposure was typically delivered accompanied by other anxiety management techniques. A multitude of optimisation strategies have been tested, yet only one of these effects (timing relative to sleep) showed preliminary evidence of replication. Conclusions: A systematic and theoretically driven program of research investigating the efficacy of exposure in young people and factors that moderate its efficacy, along with methods to overcome barriers for delivery, is urgently needed.